EFFECTS OF CATARACT SURGERY ON THE CORNEAL ENDOTHEL - Agustian Firmansyah Purnomo; Hidayat Sujuti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Manual cataract surgery techniques such as SICS and ECCE are still used today but not as many as phacoemulsification. Corneal endothelium can be damaged due to various factors during surgery such as intraoperative manuver, excessive ultrasound power, pressure during irrigation, collision between lens fragments and corneal endothelium, large air bubbles, and increased temperature during surgery. Methods: Journal articles and books in this paper were searched through various available search engines, including using searches through the sites Google Scholar, Medline, Proquest. The search method uses one or a combination of keywords, namely cataract surgery, corneal endothelial damage, corneal endothelium, specular microscope. Articles in this paper are found in English and Indonesian. Results: From several studies it can be concluded that the risk factors that greatly affect the corneal endothelium include age, race, use of contact lenses, surgery, trauma, refractive errors and anatomical abnormalities on the surface of the eyeball. Conclusion: Cataract surgery technique is significantly associated with the incidence of bullous keratopathy because the maneuvers are very prone to injuring the corneal endothel. The average percentage of damage to endothelial cells reaches 15%. This is what underlies the need for further research to find new methods that can protect the corneal endothelium.